EFFECT OF LANGGAM JAVA AND MASSASE USE GINGER MIX OLIVE OIL TO CHANGE THE LEVEL OF REUMATOID ATRITIS PAIN ON ELDERLY IN UPTD GRIYA WREDHA SURABAYA - Dany Triatmo; Pipit Festy Wiliyati; Anis Rosyiatul Husna (PROCEEDING UMSURABAYA, 2018)
Rheumatoid arthritis causes the elderly difficult to perform daily activities, elderly people with rheumatoid arthritis experience pain as much as 32.99% 1st rank of other diseases. The purpose of this study is to determine the effect of therapy Langgam Java and Massase Ginger to a decrease in pain of Rheumatoid Arthritis. Design studies using true experimental design with prepost - posttest control group design, the study population elderly who have rheumatoid arthritis in UPTD Griya Wreda Surabaya as many as 32 elderly sampling technique is simple random sampling obtained a sample of 30 respondents 15 control group and 15 experimental groups. The independent variable of Java and Massase style ginger mix olive oil. The dependent variable level of pain of rheumatoid arthritis. Data were collected using observation sheet were analyzed using the Wilcoxon Signed Rank Test and Mann Whitney U Test significant level of <0.05. The results Wilcoxon Sign Rank test show the effect of therapy Langgam Java on the scale of the pain of rheumatoid arthritis in the control group showed significant Ï = 0.005, while the influence of the style of Java and Massase ginger in the experimental group Wilcoxon Sign Rank test showed significant Ï = 0.001 so Ï <Î±, with Î± = 0.05. Identification of differences in the level of pain of rheumatoid arthritis in the control group and the experimental results were obtained significantly Wilcoxon Mann-Whitney U test Ï = 0,039 so that Ï <Î±, with Î± = 0.05.In sum, Java Langgam combination therapy and Massase Ginger in the experimental group effectively to changes in the level of pain of Rheumatoid Arthritis